Risk Factors of Postoperative Meningitis in Lateral Ventricular Trigone Meningiomas: A Clinical Analysis of 64 Patients - Han, Xiaodi; Hu, Tianhao; Wang, Run; Li, Longjie; Yu, Juanhan; Zhang, Li; Han, Sheng (Frontiers in Surgery, 2022)
Abstract Purpose: Patients with intraventricular tumors are more susceptible to postoperative meningitis (POM) than other intracranial tumors. In this study, we explored the risk factors of POM in lateral ventricular trigone meningiomas (LVTMs). Methods: Clinical features of 64 patients with LVTMs were analyzed. Age, gender, body mass index, medical history, habitual residence, marriage, highest education, intraoperative blood loss (IBL), intraventricular drainage placement, surgical duration, tumor grade, postoperative tumor cavity hemorrhage, and tumor size were included in univariate and multivariate analyses of POM. Results: Of the 64 patients, 14 patients (21.9%) received diagnosis of POM. The univariate analysis revealed IBL ≥ 400 ml (odds ratio [OR], 9.012; P = 0.003), tumor size ≥ 50 cm3 (OR, 3.071; P = 0.080), and surgical duration ≥ 5 h (OR, 2.970; P = 0.085) were considered possible risk factors for POM (P<0.10). Tumor size (R = 0.514) and surgical duration (R = 0.624) were significantly correlated with IBL (P < 0.05). In the multivariate analysis, only IBL was found to be an independent risk factor for POM. Conclusion: The IBL ≥ 400 ml is independently associated with the increased risk of POM in LVTM patients. Our results demonstrate the importance of controlling IBL for preventing POM, especially in large tumors and long surgeries.